The making of manhood among Swedish missionaries in China and Mongolia, c. 1890-c. 1914 - Sidenvall, Erik. (Studies in Christian Mission, 2009)
Over the last thirty years, issues of gender have been creatively explored within the field of mission studies. Whereas the life and work of female missionaries have been fruitfully reflected upon, male gender identity has often been understood as an unchanging category. This book offers a pioneering account of the relationship between missionary work and masculinity. By examining four individual men this study explores how self-making occurred within foreign missions, but also how conceptions of male gender informed missionary work. Changes that occurred in the lives of these men are placed within the broader context of how issues of gender were renegotiated within the contemporary missionary movement.